Why do they avoid it? Factors behind brand avoidance related to the Boycott, Divestment, and Sanctions (BDS) Movement‎ - Efendi, Pebri Anjani Rizqi; Alfansi, Lizar (Journal of Islamic Economics Lariba, 2025)
IntroductionThe escalation of the Israel–Palestine conflict in late 2023, coupled with a religious decree in Indonesia prohibiting the purchase of products affiliated with Israel, has intensified consumer-driven avoidance of certain brands. Unlike organized boycotts, brand avoidance reflects individual decisions rooted in moral, ideological, and emotional considerations. In this politically sensitive context, the Boycott, Divestment, and Sanctions movement has amplified public calls to reject brands linked to perceived human rights violations.ObjectivesThis study aims to examine the antecedents of brand avoidance among Indonesian consumers toward brands perceived to support Israel, focusing on the roles of ideological incompatibility, undesired self-congruence, social influence, and negative word of mouth, with negative emotion as a mediating variable.MethodThe research employed a quantitative approach using an online survey of 260 Indonesian respondents aged 17 years and above, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling to assess measurement validity, reliability, and the strength of hypothesized relationships.ResultsAll proposed hypotheses were supported. Negative word of mouth was the most influential factor in generating negative emotions, followed by undesired self-congruence, ideological incompatibility, and social influence. Negative emotions—such as anger, moral discomfort, and disappointment—were found to significantly predict brand avoidance, explaining 37.4% of its variance. The predictors collectively explained 44.7% of the variance in negative emotions, indicating moderate explanatory power.ImplicationsThe findings highlight the critical role of emotional responses in transforming ideological and social triggers into active brand avoidance. For brand managers, maintaining value alignment, monitoring public discourse, and engaging in transparent, ethically responsible practices are essential to mitigate reputational risks in socio-political controversies.Originality/NoveltyThis study advances understanding of brand avoidance by clarifying the mediating role of negative emotions in politically and ethically charged contexts. It provides empirical evidence from Indonesia, a Muslim-majority market, demonstrating how moral identity, social pressures, and public communication shape consumer rejection of brands tied to contentious global issues.